Coating effect on light scattering by irregularly shaped particles. (August 2018) - Shmirko, Konstantin; Pavlov, Andrey; Zubko, Evgenij
Highlights: The degree of linear polarization is sensitive to the coating material. The depolarization ratio at backscatering direction is sensitive to changes in particle size. Changes in the degree of linear polarization are in accordance with the Umov law. Abstract: In this article, we study the impact of water coating on light scattering by irregularly shaped agglomerated debris particles. We compute light-scattering properties of three types of irregular particles, which simulate atmospheric particles before and after coating. We consider two types of the Junge size distributions over sub-micron range of rc . The coating is represented as deposition of same volume of material on original particles. We found that only the degree of linear polarization is sensitive to coating type, especially maximum value of the polarization that is typically acquired at side scattering. Behavior of the degree of linear polarization maximum appears in accordance with the Umov effect. The linear depolarization ratio at backscattering direction δl is insensitive to coating material, but it is dependent from particles size.